ARTIKEL REVIEW: DENTAL IMPLANT - Halim, Susanna; Florenly, Florenly; Tarigan, Gabriel C.J.; Pratama, Rizky (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
Dental implants as a solution for tooth loss rehabilitation are increasingly developing with various approaches and techniques tailored to the clinical needs of each patient. This review article aims to summarize and analyze two recent studies on dental implants, namely the Guided Bone Regeneration (GBR) technique, and factors affecting marginal bone loss in implants. This study adopted a literature review method with a focus on case report articles related to dental implants. Data were collected from articles published over the past ten years through the Google Scholar database. The first article explored the use of GBR technique for bone augmentation in patients with mandibular bone volume deficiency. This method was shown to be effective in increasing bone volume and implant stability through the use of xenograft bone graft. The second article identifies various factors that contribute to marginal bone loss in the early postimplant stage. The analysis showed that abutment selection and retention need to consider implant positioning, aesthetics, and ease of long-term maintenance. The GBR technique has been shown to be effective in increasing the bone volume that supports implant stability, although its application still requires long-term evaluation. In addition, marginal bone loss is caused by multifactorial factors such as bone quality and the surgical technique used. Selection of the right method and an in-depth understanding of the patient's clinical condition are essential for successful dental implant therapy. ABSTRAKImplan gigi sebagai solusi untuk rehabilitasi kehilangan gigi semakin berkembang dengan berbagai pendekatan dan teknik yang disesuaikan dengan kebutuhan klinis masing-masing pasien. Artikel review ini bertujuan untuk merangkum dan menganalisis dua penelitian terbaru mengenai implan gigi, yaitu teknik Guided Bone Regeneration (GBR), dan faktor apa saja yang dapat mempengaruhi penurunan tulang marginal pada implan. Penelitian ini mengadopsi metode tinjauan literatur dengan fokus pada artikel case report terkait implan gigi. Data dikumpulkan dari artikel-artikel yang diterbitkan selama kurun waktu sepuluh tahun terakhir melalui database Google Scholar. Artikel pertama mengeksplorasi penggunaan teknik GBR untuk augmentasi tulang pada pasien dengan kekurangan volume tulang mandibula. Metode ini terbukti efektif dalam meningkatkan volume tulang dan stabilitas implan melalui penggunaan bone graft xenograft. Artikel kedua mengidentifikasi berbagai faktor yang berkontribusi terhadap marginal bone loss pada tahap awal pasca pemasangan implan. Hasil analisis menunjukkan bahwa pemilihan abutment dan retensi perlu mempertimbangkan posisi implan, estetika, dan kemudahan perawatan jangka panjang. Teknik GBR terbukti efektif untuk meningkatkan volume tulang yang mendukung stabilitas implan, meskipun penerapannya masih membutuhkan evaluasi jangka panjang. Selain itu, penurunan tulang marginal disebabkan oleh faktor multifaktorial seperti kualitas tulang dan teknik bedah yang digunakan. Pemilihan metode yang tepat dan pemahaman mendalam tentang kondisi klinis pasien sangat penting untuk keberhasilan terapi implan gigi.